2004
DOI: 10.1111/j.1939-1676.2004.tb02597.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Renin Activity and Plasma Concentrations of Aldosterone, Cortisol, Adrenocorticotropic Hormone, and α‐Melanocyte‐ Stimulating Hormone in Healthy Cats

Abstract: A pathogenetic role of the renin-angiotensin-aldosterone system has been implicated in cats in both systemic arterial hypertension and hypokalemic myopathy. Yet, measurement of plasma aldosterone concentrations (PACs) and plasma renin activity (PRA) has not unequivocally pointed to hyperaldosteronism as a cause of these conditions. To obtain appropriate reference ranges, this study included a large number (130) of healthy house cats of different breeds without a history of recent illness and plasma concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 45 publications
2
33
0
3
Order By: Relevance
“…Forty‐two cats from an animal shelter were enrolled in this study. The inclusion criteria were age ≥5 months, no remarkable findings on physical examination, systemic arterial blood pressure ≤160 mm Hg, plasma ARR below the upper reference limit (< 3.8 × 10 −9 ), 8 and laboratory results within the following reference ranges: plasma urea concentration 6.1–12.8 mmol/L, plasma creatinine concentration 76–164 μmol/L, plasma sodium concentration (Na) 146–158 mmol/L, plasma potassium concentration (K) 3.4–5.2 mmol/L, urine specific gravity (SG) >1.020, urinary total protein to creatinine ratio <10 × 10 −5 , and no remarkable abnormalities in the urine sediment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty‐two cats from an animal shelter were enrolled in this study. The inclusion criteria were age ≥5 months, no remarkable findings on physical examination, systemic arterial blood pressure ≤160 mm Hg, plasma ARR below the upper reference limit (< 3.8 × 10 −9 ), 8 and laboratory results within the following reference ranges: plasma urea concentration 6.1–12.8 mmol/L, plasma creatinine concentration 76–164 μmol/L, plasma sodium concentration (Na) 146–158 mmol/L, plasma potassium concentration (K) 3.4–5.2 mmol/L, urine specific gravity (SG) >1.020, urinary total protein to creatinine ratio <10 × 10 −5 , and no remarkable abnormalities in the urine sediment.…”
Section: Methodsmentioning
confidence: 99%
“…PAC and PRA were measured at the Department of Nephrology of the University Medical Center, Utrecht, the Netherlands, as described previously 14 and validated for the cat 8 . Briefly, for measurement of PRA, 0.5 mL of plasma was incubated at 37 °C and pH 6.0 for 1 hour, in the presence of inhibitors of angiotensinases and angiotensin I converting enzyme.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[19][20][21][22][23][24][25] Given that endog- Error bars are present but extremely small. The study reported here involved a novel assay with which changes in plasma renin concentration relative to the clinical stresses associated with renal autograft ischemia-reperfusion injury in cats were detected.…”
Section: Discussionmentioning
confidence: 99%
“…First, intra-and interlaboratory variation is substantial. 7 Strategies have been introduced to improve accuracy and efficiency of renin assays. 5 Third, because endogenous substrate (angiotensinogen) is used, the concen-tration of substrate may be a limiting factor 5 ; regardless of the total amount of substrate, the concentration of angiotensinogen affects the enzyme kinetics of renin and may cause variation in results.…”
mentioning
confidence: 99%